Infill Housing: A Design for Savannah's Victorian District - Bob Burnham (Oz, 1982)
This design for infill housing was developed in response to the Historic Savannah Foundation's Residential Design Competition for the city's Victorian District. The competition's objective was to stimulate creation of designs which would be at home in the district and would also be feasible for private development...